Advanced organic chemistry reactions and mechanism - Miller, Bernard (Prentice Hall, 1998)
*Ideal text for all undergraduate and graduate students who have previously taken a one-year course in Organic Chemistry, as well as serving students who have already had specialized courses in Physical Organic Chemistry, Stereochemistry, Spectroscopy, etc., and who need additional knowledge about Organic Reactions. Typically taught as a third semester undergraduate course or a senior/graduate course in organic reactions and mechanisms. *This text discusses important organic reactions and mechanisms not usually covered in depth in introductory organic chemistry courses. By stressing new material, it avoids student's hostility to repeating material previously studied, while still offering the opportunity to review important concepts and principles in novel settings.